Net effects : how librarians can manage the unintended consequences of the Internet - Block, Marylaine, 1943- (Information Today, 2003)
"The Internet is a mixed blessing for libraries and librarians. On the one hand, it provides opportunities to add services and expand collections; on the other, it has increased user expectations and contributed to techno stress. Today, the Net is challenging librarians' ability to select, threatening the survival of the book, necessitating continuous retraining, presenting new problems of access and preservation, putting new demands on budgets, and embroiling information professionals in legal controversies. In Net Effects, librarian, journalist, and Internet guru Marylaine Block examines the issues and brings together a wealth of insights, war stories, and solutions. Almost 50 articles by dozens of imaginative librarians-expertly selected, annotated, and integrated by the editor-suggest practical and creative ways to deal with the range of Internet "side effects," regain control of the library, and avoid being blindsided by technology again."--